DETERMINATION OF SIMVASTATIN IN HUMAN PLASMA USING LIQUID CHRMATOGRAPHY-MASS SPECTROMETRY - KHALED. M. ALAKHALI (International Journal of Pharma and Bio Sciences, 2014)
A simple, sensitive and selective liquid chromatography with mass spectrometry used for determination simvastatin in human plasma has been developed, after extraction simvastatin by ethyl acetate and hexane (90:10%, v/v) using lovastatin as internal standard. Solutes are separated on a C18 column with mobile phase consisting of mixture of acetonitrile and water (75:25%, v/v) 500 μL/min. Adduct product ions was detected by selected reaction monitoring in positive ion mode (m/z: 436 and m/z: 422 for simvastatin and lovastatin respectively). The calibration curve was linear from 0.5-20 ng/mL. The entire run time for analysis was only 5 min. The lower limit of quantitation of 0.5ng/mL was achieved. Precision and accuracy for the assay were determined by the intra-day and inter-day variation at three concentrations of 3, 6 and 12 ng/mL. The intra-day coefficients of variation were found to be less than 10% and the accuracies were between 97.50% and 109.50%. The inter-day coefficients of variation were found to be less than 10% and accuracies were found to be between 98.30% and 106.60%. The liquid chromatography with mass spectrometry method for the determination of simvastatin in human plasma offers several unique aspects. The separation is simple and rapid. The volume of plasma sample used in the assay is only 200 μL